Fallacious, misleading and unhelpful: The case for removing ‘systematic review’ from bioethics nomenclature - Birchley, Giles (Bioethics, 2022)
Attempts to conduct systematic reviews of ethical arguments in bioethics are fundamentally misguided. All areas of enquiry need thorough and informative literature reviews, and efforts to bring transparency and systematic methods to bioethics are to be welcomed. Nevertheless, the raw materials of bioethical articles are not suited to methods of systematic review. The eclecticism of philosophy may lead to suspicion of philosophical methods in bioethics. Because bioethics aims to influence medical and scientific practice it is tempting to adopt scientific language and methods. One manifestation is the increasing innovation in, and use of, systematic reviews of ethical arguments in bioethics. Yet bioethics, as a broadly philosophical area of enquiry, is unsuited to systematic review. Bioethical arguments are evaluative, so notions of quality and bias are inapplicable. Bioethical argument is conceptual rather than numerical, and the classification of concepts is itself a process of argument that cannot aspire to neutrality. Any ‘systematic review’ of ethical arguments in bioethics thus falls short of that name. Furthermore, labels matter. Although the bioethics research community may find that adopting the language and the outward methods of clinical science offers apparent prospects of credibility, policy influence and funding, we argue that such misdirection carries risks and is unlikely to pay dividends in the long term. Bioethical sources are amenable to the review methods of the social sciences, and it is on these methods that specific methods of bioethics literature review should be built.